Body Height Prediction Model from Foot Measurements in a Chilean Population of University Student Athletes - Sanchez-Ramirez, C (Asociacion de Antropologia Biologica Argentina, 2024)
In forensic research, it is important to identify human remains. Body height is an essential aspect in anthropometric characterization. This is the first study in a Chilean population and aimed to develop a height estimation model for a young adult population of athletes from foot measurements. Central Chilean subjects were included (n=139). Height (H), Foot Length (FL), Foot Breadth (FB), and Heel Foot Breadth (HFB) were measured. For both sex and feet, FL was the most correlated with H (Females r > .8, p < .001; Males r > .7, p < .001). When only FL is used in the equation, similar values are obtained as when using FL + FB + HFB in females (R2 > 65%) and males (R2 > 51%). It was possible to appreciate that the mean of the data obtained from the equations is equal to the mean of the actual data. However, the minimum values tend to be overestimated, and the maximum values tend to be underestimated. It was possible to develop a mathematical model that allows predicting height from the anthropometric measurements of the feet of young adult athletes from the Metropolitan Region of Chile. Furthermore, it was shown that foot length was the measurement most correlated with height and can be used independently in the equations. This study provides valuable information in the forensic medical field, specifically in the identification of bodies in which it is impossible to determine the height directly because they are dismembered or incomplete. © 2024 Asociacion de Antropologia Biologica Argentina. All rights reserved.